Psychosocial factors influencing risk-taking in middle age for STIs. (7th July 2016) - Dalrymple, Jenny; Booth, Joanne; Flowers, Paul; Lorimer, Karen
Abstract : Objectives: To increase the knowledge of the psychosocial factors influencing sexual risk-taking for STIs among adults in late middle age. Methods: Individual interviews were conducted either face to face or by telephone with 31 heterosexual men and women aged between 45 and 65. They were recruited from NHS sexual health services (n=16) and council run culture and leisure facilities (n=15) in a large Scottish city. A total of 18 women and 13 men were interviewed. All interviews were transcribed in full and thematically analysed. Results: Analysis detailed important psychosocial and sociocultural factors; the prioritisation of intimacy above and beyond concerns about risks for STI in sexual partnerships; the importance of unwanted pregnancy in shaping risk perceptions throughout the life course; vulnerability associated with periods of relationship transition (eg, bereavement, divorce or separation); social norms and cultural expectations relating to age-appropriate sexual and health-seeking behaviours. Conclusions: This is the first qualitative study to examine the factors associated with sexual risk-taking among heterosexual adults in late middle age in the UK. Many factors associated with sexual risk-taking are similar to those reported within other populations. However, we also detail population-specific factors, which should be considered in terms of the development of interventions for 'at risk' older adults, or the tailoring of wider behaviour change interventions to this specific age group.